Influence of Synthesis Conditions on Electrochemical Properties of P2‐Type Na2/3Fe2/3Mn1/3O2 for Rechargeable Na Batteries. Issue 4 (2nd May 2018) - Zhao, Wenwen; Tsuchiya, Yuka; Yabuuchi, Naoaki
Abstract: P2‐type Na2/3 Fe2/3 Mn1/3 O2 samples are synthesized by solid‐state calcination with different conditions and the influence of synthesis conditions on the structural and electrochemical properties is systematically studied. By controlling the synthesis conditions, a fraction of O3‐type impurity phase is effectively decreased, and nearly stoichiometric P2 Na2/3 Fe2/3 Mn1/3 O2 is successfully obtained by a two‐step calcination method. A voltage plateau of 2.5 V, which is attributed to the oxidation of Mn 3+ to Mn 4+, appears in initial charge profiles for quenched and one‐step calcined samples. In contrast, for the initial charge process, the voltage plateau of 2.5 V is not observed in the sample prepared in the two‐step calcination process, suggesting that Mn 3+ is not contained in this sample. Charge/discharge mechanisms of nearly stoichiometric Na2/3 Fe2/3 Mn1/3 O2 are also examined by X‐ray absorption spectroscopy and X‐ray diffractometry, and it is found that reversible redox reaction of Fe 3+ /Fe 4+ and Mn 3+ /Mn 4+ proceeds on electrochemical cycles. Moreover, stacking faults associated with metal layer glide on charge are more pronounced for P2 Na2/3 Fe2/3 Mn1/3 O2 in comparison to the P2‐type Mn‐rich system, Na2/3 Fe1/2 Mn1/2 O2 . From these results, factors affecting electrode performance of sodium insertion materials are discussed. Abstract : Na2/3 Fe2/3 Mn1/3 O2 is synthesized under different conditions as a potential cost effective positive electrode material for rechargeable sodium batteries. Nearly stoichiometric Na2/3 Fe2/3 Mn1/3 O2 is successfully prepared via a two‐step calcination method. Electrochemical properties and reaction mechanisms of Na2/3 Fe2/3 Mn1/3 O2 in Na cells are carefully examined. From these results, factors affecting sodium storage properties are discussed.